Interest in and uptake of genetic counseling for preconception carrier screening when offered to predominantly white reproductive‐age persons seeking gynecologic care at a single U.S. academic medical center. Issue 1 (5th July 2021) - Nesbit, Carleigh B.; Pollack, Catherine C.; Mascia, Nicolina S.; LaCroix, Valerie H.; Applebee, Devin M.; Bosco, Amy W.; Wilkinson‐Ryan, Ivy; Erekson, Elisabeth D.; Evans, Rebecca H.
Abstract: The objective of this study was to assess the level of interest in preconception carrier screening among reproductive‐aged persons presenting for gynecologic care and to identify demographic factors predictive of pursuing screening. Patients aged 18–40 who were presenting for gynecologic care at a single U.S. academic medical center were provided with information about current options for preconception carrier screening and were offered genetic counseling referral with the possibility to undergo screening. Outcomes of interest were desire for genetic counseling referral and attendance at genetic counseling visit. Statistical analyses were performed as appropriate using R version 3.6.1 with variables significant at 0.1 included in a multivariable logistic regression. Of 193 participants, 79 (41%) desired genetic counseling referral. Participants aged 25–34 (OR 3.39, 95% CI 1.47–8.10) and nulliparas (OR 2.69, 95% CI 1.23–6.03) were more likely to desire referral. Thirty‐five participants (44.3% of those who desired referral) attended a visit with genetic counseling. Having an advanced degree (OR 3.27, 95% CI 1.06–10.4) was associated with visit attendance. Thirteen participants underwent screening, and five were found to be a carrier of at least one X‐linked or autosomal recessive condition. Surprisingly, presenting for a gynecologic visit directly related to planning a pregnancy was not associated with increased interest in preconception carrier screening. Nulliparas and those aged 25–34 likely expressed greater interest in referral due to high potential for future childbearing in these groups. The increased level of visit attendance in participants with advanced degrees is likely confounded by the high level of health literacy and financial resources in this group.